Teaching at School: between equality and diversity. An approach from political cultural Pedagogy (Praxis Educativa, 2012)
In the area of Pedagogy, the problem of the dicotomies: equality-unequality; diversity-homogenity, has brought a wide variety of debates and has given place tointeresting papers that help understand its complexity and give meaning to thenecesity of elucidating these questions In this sense, the intention of our work,is to contribute with some conceptual elements that could be useful to set someideas about the mentioned dualities and at the same time, support practices facingthese confl icts and integrate them into a wider scheme making a commitmentof action in the classrooms. To make a brief socio political analysis of our country,we focus in the real possibilities of teaching at school, from a political culturalapproach which recognizes social diff erences, considers diversity, and proposes–in the complexity of a classroom cultural production with its particularhistoies, experiencies, and multicultural languages– to build a cultural net able topromote critical refl ective learning with a democratic training that gives citizensequality of opportunities.
Keywords: History; teaching; inclusion; experts; teachers